Generative Design of Articulated Rod of Radial Engine - Rai, Sawan Kumar; Keawmuang, Harit; Variyavwala, Himanshu; Shatnawi, Laith (International Journal of Engineering and Management Sciences, 2021)
The constant need for improvement drives humans to look for the best possible option in every field. Computer Aided Design (CAD) is no exception, to follow the best method of designing a product and finalizing it, researchers came up with an idea to generate multiple designs using fixed input values and finalizing the most appropriate one. The objective is achieved using an iterative design process based on algorithms by a specific software. Generative design introduces a new experience based on the Integration of machine dynamics in the manufacturing of objects and about experience. In this work generative design method was investigated on an articulated rod, one of the most important components of the rotary engine, to effectively improve the overall working performance of the engine and enhance its performance by decreasing its mass. Since fuel consumption by the machine can be greatly reduced by lowering the mass, so the goal is to minimize the weight of the rod while mechanical characteristics have to be within the acceptable values. Also, finite element analysis (FEA) was investigated on the part as to ensure the reliability of the rod before and after optimization.